Microwave processing of lunar soil for supporting longer-term surface exploration on the Moon. (August 2016) - Srivastava, Vibha; Lim, Sungwoo; Anand, Mahesh
Abstract: The future of human space exploration will inevitably involve longer-term stays and possibly permanent settlement on the surfaces of other planetary bodies. It will, therefore, be advantageous or perhaps even necessary to utilise local resources for building an infrastructure for human habitation on the destination planetary body. In this context human lunar exploration is the next obvious step. Lunar soil is regarded as an ideal feedstock for lunar construction materials. However, significant gaps remain in our knowledge and understanding of certain chemical and physical properties of lunar soil, which need to be better understood in order to develop appropriate construction techniques and materials for lunar applications. This article reviews our current understanding of the dielectric behaviour of lunar soil in the microwave spectrum, which is increasingly recognised as an important topic of research in the Space Architecture field. Although the coupling between the lunar soil and microwave energy is already recognised, considerable challenges must be overcome before microwave processing could be used as a main fabrication method for producing robust structures on the Moon. We also review the existing literature on the microwave processing of lunar soil and identify three key research areas where future efforts are needed to make significant advances in understanding the potential of microwave processing of lunar soil for construction purposes.